Immune Reconstitution Inflammatory Syndrome Unmasking or Worsening AIDS-Related Progressive Multifocal Leukoencephalopathy: A Literature Review - Fournier, Anna; Martin-Blondel, Guillaume; Lechapt-Zalcman, Emmanuèle; Dina, Julia; Kazemi, Apolline; Verdon, Renaud; Mortier, Emmanuel; de La Blanchardière, Arnaud (Frontiers in Immunology, 2017)
Incidence of progressive multifocal leukoencephalopathy (PML) in HIV-infected patients has declined in the combined antiretroviral therapy (cART) era although a growing number of AIDS-related PML-immune reconstitution inflammatory syndromes (PML-IRIS) has been published during the same period. Therapeutic management of PML-IRIS is not consensual and mainly relies on corticosteroids. Our main aim was, in addition to provide a thoughtful analysis of published PML-IRIS cases, to assess the benefit of corticosteroids in the management of PML-IRIS, focusing on confirmed cases. We performed a literature review of the 46 confirmed cases of PML-IRIS cases occuring in HIV-infected patients from 1998 to September 2016 (21 unmasking and 25 paradoxical PML-IRIS). AIDS-related PML-IRIS patients were mostly men (sex ratio 4/1) with a median age of 40.5 years (Range 12-66). Median CD4 T cell count before cART and at PML-IRIS onset was 45/µl (0-301) and 101/µl (20-610) respectively. After cART initiation, PML-IRIS occurred within a median timescale of 38 days (18-120). Clinical signs were: motor deficits (69%), speech disorders (36%), cognitive disorders (33%), cerebellar ataxia (28%) and visual disturbances (23%). Brain MRI revealed hyperintense areas on T2-weighted sequences and FLAIR images (76%) and suggestive contrast enhancement (87%). PCR for JC virus (JCV) in CSF was positive in only 84% of cases; however, when performed, brain biopsy confirmed diagnosis of PML in 90% of cases and demonstrated histological signs of IRIS in 95% of cases. Clinical worsening related to PML-IRIS and leading to death was observed in 28% of cases. Corticosteroids were prescribed in 63% of cases and maraviroc in one case. Statistical analysis failed to demonstrate significant benefit from steroid treatment, despite spectacular improvement in certain cases. Diagnosis of PML-IRIS should be considered in HIV-infected patients with worsening neurological symptoms after initiation or resumption of effective cART, independently of CD4 cell count prior to cART. If PCR for JCV is negative in CSF, brain biopsy should be discussed. Only large multicentric randomized trials could potentially demonstrate the possible efficacy of corticosteroids and/or CCR5 antagonists in the management of PML-IRIS.